Consideration of particle rearrangement during the modeling of spark plasma densification of Al–Mg alloy powders. (June 2015) - Hendrickx, P.; Milligan, J.; Brochu, M.
Abstract : A constitutive model of powder densification during spark plasma sintering was adapted to introduce the contribution of particle rearrangement. Such contribution was quantified by a particle-packing factor describing changes in packing states upon compaction of spherical and non-spherical powder particles. To validate this addition, atomized and cryomilled aluminum–magnesium powders were sintered using single-step and two-step sintering schedules. Densification simulations of each powder and sintering schedule agreed well with experimental results, supporting the proposed description of the particle rearrangement contribution.